Dragon Ops - Mancusi, Mari (Little, Brown, and Company, 2021)
Twelve-year-old Ian is thrilled to beta test the mixed-reality version of his favorite game, but unless he, his sister, Lilli, and their cousin Derek defeat the dragon, it will be game over.